Development of Instruments for Learning Independence for High School Students: Construct Validity and Reliability - Zafrullah; Ersa Mayola; Rizki Tika Ayuni; Cheequitha Adhelia (Penerbit Hellow Pustaka, 2023)
Improving the quality of education involves various methods, and one of them is the use of instruments as measuring tools. This instrument has an important role in improving students' learning experience. This research aims to develop an instrument for learning independence for high school students. This research uses an instrument for independent learning which consists of six aspects. The number of samples used was 233 high school students in Natuna, Riau Islands, Indonesia. The data analysis technique is to prove content validity, construct validity and reliability. The final results of the learning independence instrument have gone through the stages of content validity and construct validity, so that the results obtained are in the valid category with two analyzes on construct validity, and reliability is in the category that has passed 0.7. The weakness in this research is that the trial was only carried out once, and needed to be repeated to get an instrument that was truly standard and suitable for use.